2018
DOI: 10.1016/j.chom.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The MAP4 Kinase SIK1 Ensures Robust Extracellular ROS Burst and Antibacterial Immunity in Plants

Abstract: Microbial patterns are recognized by cell-surface receptors to initiate pattern-triggered immunity (PTI) in plants. Receptor-like cytoplasmic kinases (RLCKs), such as BIK1, and calcium-dependent protein kinases (CPKs) are engaged during PTI to activate the NADPH oxidase RBOHD for reactive oxygen species (ROS) production. It is unknown whether protein kinases besides CPKs and RLCKs participate in RBOHD regulation. We screened mutants in all ten Arabidopsis MAP4 kinases (MAP4Ks) and identified the conserved MAP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(120 citation statements)
references
References 75 publications
(123 reference statements)
3
107
0
Order By: Relevance
“…In particular, BIK1 phosphorylates RBOHD residues S343 and S347, and CPKs phosphorylate RBOHD residues S163 and, possibly, S347 during PTI. Recently, it was found that the MAP4K SIK1 is also involved in the full phosphorylation on S339 and S347 during PTI (M. Zhang et al, 2018).…”
Section: Overlap In Rps2-and Fls2-induced Phosphorylation Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, BIK1 phosphorylates RBOHD residues S343 and S347, and CPKs phosphorylate RBOHD residues S163 and, possibly, S347 during PTI. Recently, it was found that the MAP4K SIK1 is also involved in the full phosphorylation on S339 and S347 during PTI (M. Zhang et al, 2018).…”
Section: Overlap In Rps2-and Fls2-induced Phosphorylation Sitesmentioning
confidence: 99%
“…It would be interesting to investigate the involvement of these RLCKs in RBOHD phosphorylation using multiple knockout mutants. Interestingly, the MAP4 kinase SIK1 has been found recently to be able to phosphorylate RBOHD during PTI (M. Zhang et al, 2018). However, it remains to be elucidated whether SIK1 contributes to RBOHD phosphorylation during ETI.…”
Section: Rps2 and Fls2 Trigger Similar Phosphorylation Patterns At Immentioning
confidence: 99%
“…The authors also found that map4k3/sik1 mutants showed an autoimmune phenotype only under specific conditions, indicating that growth conditions affect MAP4K3 function. Furthermore, flg22-induced BIK1 activation is decreased in map4k4, but not map4k3 [40], indicating that BIK1 hyper-phosphorylation was dependent on MAP4K4 but not MAP4K3. Comparing map4k3 and map4k4 mutants, they show some common phenotypes.…”
Section: Discussionmentioning
confidence: 95%
“…Similar to MAP4K4, MAP4K3/SIK1 was recently reported to positively regulate flg22-induced immunity responses by stabilizing BIK1 [40]. To determine the genetic redundancy between MAP4K3 and MAP4K4, we generated map4k3 map4k4 double mutants ( Fig 6E).…”
Section: Map4k3/sik1 Functions With Map4k4 In Regulating Bik1mediatedmentioning
confidence: 99%
“…Specifically, RBOHD S347 site is in CPK phosphorylation motif (φ‐X‐X‐X‐X‐S/T‐X‐B; Kadota et al ., ), and CPK5 was involved in the phosphorylation (Adachi & Yoshioka, ) while RBOHD S343 is not in the typical CPK phosphorylation motif. A more recent study suggested that Arabidopsis MAP4 kinase SIK1 positively regulated ROS production by phosphorylating RBOHD S347 during PTI (Zhang et al ., ). Thus, these mentioned kinases may phosphorylate RBOHD during ETI, perhaps in a redundant manner.…”
Section: How Is Rbohd Phosphorylation Regulated In Nlr Signalling?mentioning
confidence: 97%